2016
DOI: 10.1016/j.jelechem.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyano dipolar groups on the performance of lithium-ion battery electrospun polyimide gel electrolyte membranes

Abstract: Effect of cyano dipolar groups on the performance of lithium-ion battery electrospun polyimide gel electrolyte membranes AbstractThree polyimide membranes (polymer 0CN, copolymers 0CN/2CN (50/50) and polymer 2CN), with and without [Formula presented] dipolar groups, have been prepared by electrospinning and evaluated as lithiumion battery separators. The prepared membranes show average fiber diameters between 0.5 and 1.09 μm and a degree of porosity of ~ 80%. The thermal stability, uptake, tortuosity and ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
(50 reference statements)
0
11
1
Order By: Relevance
“…Further investigation found that the high ionic conductivity could be associated with the good affinity of PI 11a, which holds liquid electrolyte via coordination through electrostatic interactions; thus, it results in higher electrolyte retention and uptake. 148 Maceiras et al 149 reported the copolymerization of two aromatic diamines, 1,3bis-2-cyano-3-(3-aminophenoxy)phenoxybenzene (diamine 2CN) and 1,3-bis(3-aminophenoxy)benzene (diamine 0CN) with 4,4′-oxidiphtalic anhydride (ODPA) to synthesize a new amorphous PI 11b for elucidating the effect of the cyano group (-CN) on the electrochemical performance of GPEs. 149 The resulting PI 11b was further prepared as a fiber using electrospinning process by dissolving in N,N-dimethylformamide and DMAc (1:1, v/v).…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further investigation found that the high ionic conductivity could be associated with the good affinity of PI 11a, which holds liquid electrolyte via coordination through electrostatic interactions; thus, it results in higher electrolyte retention and uptake. 148 Maceiras et al 149 reported the copolymerization of two aromatic diamines, 1,3bis-2-cyano-3-(3-aminophenoxy)phenoxybenzene (diamine 2CN) and 1,3-bis(3-aminophenoxy)benzene (diamine 0CN) with 4,4′-oxidiphtalic anhydride (ODPA) to synthesize a new amorphous PI 11b for elucidating the effect of the cyano group (-CN) on the electrochemical performance of GPEs. 149 The resulting PI 11b was further prepared as a fiber using electrospinning process by dissolving in N,N-dimethylformamide and DMAc (1:1, v/v).…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
“…148 Maceiras et al 149 reported the copolymerization of two aromatic diamines, 1,3bis-2-cyano-3-(3-aminophenoxy)phenoxybenzene (diamine 2CN) and 1,3-bis(3-aminophenoxy)benzene (diamine 0CN) with 4,4′-oxidiphtalic anhydride (ODPA) to synthesize a new amorphous PI 11b for elucidating the effect of the cyano group (-CN) on the electrochemical performance of GPEs. 149 The resulting PI 11b was further prepared as a fiber using electrospinning process by dissolving in N,N-dimethylformamide and DMAc (1:1, v/v). After being activated by immersion into 1 M LiPF 6 in EC/DMC (1:1, v/v), the resulting GPE exhibited an ionic conductivity of 0.7 × 10 −3 S cm −1 at room temperature and a higher degree of porosity up to ∼80%.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these polymers, other synthetic polymers such as polyimide (PI) [40], poly (ether ether ketone) (PEEK) [41], polyetherimide (PEI) [42], polybenzimidazole (PBI) [43] and poly (m-phenylene) isophthalamide) (PMIA) [44] have been used to increase the thermal stability of the separator membranes, among other relevant parameters.…”
Section: Membrane Structure and Characteristics For Lithium-ion Batteriesmentioning
confidence: 99%
“…It is well known that polar cyano groups (–CN) have large dipole moment and polarizability; thus, they can form stable complex through hydrogen bonds and strong intermolecular forces. 14 17 In addition, the cyano-containing polymers usually have strong interaction with the matrix, when they work as coating materials. 18 It is of interest to introduce the –CN groups into high-performance polymers to enhance their adhesive strength and other properties, especially when they used as functional coatings and multilayer films.…”
Section: Introductionmentioning
confidence: 99%